Toothbrushing behavior over time: A correlational analysis of repeatedly assessed brushing performance - Weik, Ulrike; Sämann, Thorben; Eidenhardt, Zdenka; Shankar Subramanian, Sadhvi; Wöstmann, Bernd; Margraf-Stiksrud, Jutta; Deinzer, Renate; Justus Liebig University Giessen (My University, 2024)
Effective toothbrushing is important for maintaining good oral health. Nonetheless, epidemiological data suggest that individuals often encounter challenges in achieving oral cleanliness when brushing their teeth. Various cross-sectional studies have observed brushing behavior of individuals and found some widespread behavioral deficits including neglect of inner surfaces and inconsistent brushing movements. However, longitudinal studies exploring the consistency of these deficits over time are currently lacking. Therefore, this study investigated the intra-individual stability of toothbrushing performance by repeated observation of 105 students during two brushing appointments (T1/T2) two weeks apart. One-half of the participants (n = 52) were instructed to brush to the best of their ability, while the other half were directed to brush as usual (n = 53). Calibrated observers analyzed brushing duration, brushing movements (horizontal, circular, vertical), brushing time on tooth surfaces (outer, inner, occlusal), and distribution of time across sextants. Correlational analyses revealed a high intra-individual stability of all parameters in both groups. Correlation coefficients varied between r = 0.72 (horizontal movements at outer surfaces) and r = 0.93 (total tooth contact time). All correlations were statistically significant (p < 0.001). The results indicated that specific individual toothbrushing patterns were developed by the participants. It is important that preventive measures take into account the challenge of changing such established habits. Healthcare professionals and patients should recognize this challenge when addressing oral hygiene deficiencies.
Keywords: ddc:150